Assessment of ecosystem integrity of lowland dipterocarp forest ecosystem using remote sensing - Abdul Razak, Muhammad Azmil (2021)
Ecosystem Integrity Index (EII) is a concept to determine the quality or the health of an ecosystem. The EII development can assist forest managers and decision makers in the conservation effort and forest management in Malaysia through the development of a simple and easy-to-adopt index. The aim of this study is to assess and evaluate the EII through the development of forest structure empirical models from remotely sensed data for lowland dipterocarp forest in Malaysia. The objectives of this study are: (i) to assess the structure and composition of lowland dipterocarp forest in Malaysia, (ii) to develop empirical model for estimating stand structure from remotely sensed data, and (iii) to derive the ecosystem integrity index for lowland dipterocarp forest. Tree Basal Area (BA), aboveground biomass (AGB) and volume plot from plot data were used as dependent variables, while remote sensing data from Landsat, Pleiades and LiDAR were used as independent variables for model development. Tree plot census was carried out from 17 to 19 May 2016, while remote sensing data acquisition dates for Landsat, Pleiades and LiDAR were 13 March 2016, 24 January 2015 and April 2015 respectively. Forest Structure Modeling was carried out by means of a correlation analysis with the calibration of dependent and independent data to select the most significant and accurate remote sensing variables to derive empiric equation (model), fitting stage to select the best model with the highest coefficient of determination (R2) and the lowest root mean square error ( RMSE) validation of the final selected. The Ecosystem Integrity Index was developed by the average percentage of the predicted BA, AGB and model volume. The EII was categorised at five integrity levels as high (81–100%), medium high (61–80%), moderate (41–60%), medium low (21–40%) and low (0–20%). A total of 1035 trees with diameter at breast height (DBH) of 5.0 cm and above were recorded in 69.115 ha sampling areas. The total trees recorded represented 150 species from 87 genera and 34 families. Shorea macroptera (Dipterocarpaceae), S. leprosula (Dipterocarpaceae) and S. parviflora (Dipterocarpaceae) are three dominant species, with Species Important Value Index (SIVi) of 6.49%, 6.23% and 5.51%, respectively. Dipterocarpaceae is the most dominant with Family Important Value Index (FIVi) of 33.54%. The developed final model is robust and consistent with high R2 with range of 0.84 to 0.87. The final models constructed for AGB, BA and volume value of R2 are 0.85, 0.84 and 0.87 respectively. The RMSE of AGB, BA and volume model are 53.1 Mg/ha, 3.54 m2/ha and 46.4 m3/ha, respectively. The overall stand AGB, BA and volume for Sungai Menyala Forest Reserve is 282.29 Mg/ha, 17.68 m2/ha and 239.51 m3/ha. An Ecosystem Integrity Index (EII) assessment has been successfully demonstrated by this study with production of practical, multi-scaled, flexible, adjustable and policy-relevant index. The overall EII of Sungai Menyala Forest Reserve is in Category 3, which shows that the area is within the medium value.